2010
DOI: 10.1111/j.1751-9004.2010.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Religious Prosociality: A Review and Reformulation

Abstract: Historically, religion and religious belief have often been credited as the source of human morality. But what have been the real effects of religion on prosocial behavior? A review of the psychological literature reveals a complex relation between religious belief and moral action: leading to greater prosocial behavior in some contexts but not in others, and in some cases actually increasing antisocial behavior. In addition, different forms of religious belief are associated with different styles of co‐operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 61 publications
8
147
0
3
Order By: Relevance
“…In line with previous findings we found that Protestants scored higher on self-report measures of prosocial behavior (i.e., the total amount of money donated to charities) than Catholics (Bekkers & Schuyt, 2008;Bekkers & Wiepking, 2011b;Hoge & Yang, 1994;Zaleski & Zech, 1994)-also when looking selectively at donations to religious charities, in line with the parochial view of religious prosociality (Preston et al, 2010). Contrary to our initial hypothesis, we did not find evidence that denominational differences in prosocial behavior were related to our measures of self-esteem and self-signaling.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous findings we found that Protestants scored higher on self-report measures of prosocial behavior (i.e., the total amount of money donated to charities) than Catholics (Bekkers & Schuyt, 2008;Bekkers & Wiepking, 2011b;Hoge & Yang, 1994;Zaleski & Zech, 1994)-also when looking selectively at donations to religious charities, in line with the parochial view of religious prosociality (Preston et al, 2010). Contrary to our initial hypothesis, we did not find evidence that denominational differences in prosocial behavior were related to our measures of self-esteem and self-signaling.…”
Section: Discussionsupporting
confidence: 92%
“…Unscrambling sentences which contain God-related concepts increase willingness to volunteer for environmental cause (Sasaki et al, 2011). Priming with religious words also reduced cheating (Randolph-Seng & Nielsen, 2007), and increased donations (Hernandez & Preston, 2010 as cited in Preston, Ritter, & Hernandez, 2010). These religious priming studies indicate that activating religious representation through religion-related words may have semantically activated prosocial behaviors (Pichon et al, 2007;Shariff & Norenzayan, 2007).…”
Section: International Journal Of Research Studies In Psychologymentioning
confidence: 74%
“…A bulk of studies already have found consistent link between religiosity and prosocial behaviors (for a recent review, see Hernandez, 2010 andSaroglou, 2013). For example, religiosity facilitates everyday minimal-cost helping (Batara, 2015), cooperation and generosity (Ahmed, 2009), and even philanthropy (Lincoln, Morrissey, & Mundey, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Prosociality is built into the tenants of most religions. In fact, some feel that religion is the source of morality, which leads to prosocial behavior (Preston, Ritter, & Hernandez, 2010). Indeed, religious people believe themselves to be prosocial (Batson, Schoenrade, & Ventis, 1993), most likely because this is seen as important to their god (Shariff & Norenzayan, 2007).…”
Section: Current Studymentioning
confidence: 99%